COMP-12. SINGLE-CELL TRANSCRIPTOME PROFILING OF GBM TISSUE ACUTE SLICE CULTURES FOR PERSONALIZED DRUG SCREENING. (11th November 2019) - Zhao, Wenting; Spinazzi, Eleonora; Dovas, Athanassios; Upadhyayula, Pavan; Marie, Tamara; Sisti, Michael; Bruce, Jeff; Canoll, Peter D; Sims, Peter
Abstract: Glioblastoma (GBM) is the most common and malignant type of primary brain tumor, and more effective treatment options are needed. Both inter- and intratumoral heterogeneity present major challenges to the application of targeted therapies in GBM. Therefore, precision medicine approaches to GBM would benefit significantly from the ability to predict drugs or drug combinations that target specific subpopulations of tumor cells. Model systems, such as adherent cell lines, neurospheres, patient-derived xenografts (PDXs), and patient-derived organoids, have been reported as platforms for drug screening and accessing drug responses. However, these models do not recapitulate the full heterogeneity of GBM tissue, lack key components of the tumor microenvironment or take weeks to months to establish, which limits the predictive power of drug response assays or delays clinical decision-making. To address these limitations, we are combining ex vivo slices of intact, patient-derived GBM tissue with single-cell RNA-seq (scRNA-seq) for small-scale drug screening and assessment of patient- and cell type-specific drug responses. We generated slices from both preclinical mouse glioma models and surgical specimens from GBM patients and showed that acute slices preserved both the tumor heterogeneity and tumor microenvironment observed in scRNA-seq of cells directly isolated from tumor tissue. To test drug responses, we treated tissue slices from GBM mouse models and five different patients with six drugs for 18hr. By performing scRNA-Seq and analyzing transcriptional profiles of treated and untreated control slices, we identified drug-induced transcriptional responses in specific subpopulations of tumor cells, patient-specific drug sensitivities, and drug effects conserved in both mouse and human tumors. The GBM tissue slices were generated immediately following surgical resection, and experiments were completed within 24 hours. With these features, our method is attractive for rapidly accessing cell type- and patient-specific drug responses and has potential for preclinical drug screening and guiding personalized treatment for GBM.